Revisiting the Severe Classification of Abū Ḥātim al-Rāzī: an Analysis of Technical Terminology in Ḥadīth Transmitter Criticism - Jamilin, Ahmad Kamil Bin (Al-Bayān, 2020)
Abū Ḥātim Muḥammad b. Idrīs al-Rāzī was a leading figure in the science of ḥadīth transmission and considered among the early generation in ḥadīth transmitter criticism (what are known as al-ǧarḥ wa al-taʿdīl, impugning and approving). However, later ḥadīth scholars classified Abū Ḥātim as a mutašaddid (severe) ḥadīth critic, based on his abundant evaluations and criticisms of the ḥadīth transmitters. The evaluation of his criticism is sometimes ambiguous and sometimes supplemented by clear statements and proofs. This ambiguity usually occurs as a result of the sophisticated terminologies, different uses of multiple meanings of a word, inconsistencies and the unusual presence of contradictions. This matter may lead to confusion and misunderstanding among contemporary scholars and students of ḥadīth transmitter criticism. Among the terms he used were ‘laysa bi al-qawī’ and ‘laysa bi qawī’, which literally means ‘not strong’ and deny the credibility of a transmitter, or totally rejects his or her ḥadīth. However, based on our exploratory analysis of how Abū Ḥātim employed those terms, they cannot be accepted in a literal sense. Therefore, this article aims to thoroughly scrutinize the severity of Abū Ḥātim when he evaluates a transmitter in comparison to other master ḥadīth critics. To summarize, Abū Ḥātim’s terminology is very important for understanding his methodology, which certainly has an impact on ḥadīth transmitter criticism as well as the ultimate goals of al-ǧarḥ wa al-taʿdīl, i.e., the authenticity of prophetic ḥadīth.